10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
Background Appropriate reproductive management is essential for improving pregnancy outcomes and neonatal survival in dogs. However, information on the practices adopted by Italian dog breeders remains limited. Objectives This study aimed to describe reproductive and neonatal management practices among certified Italian dog breeders, compare them across Northern, Central and Southern Italy, and assess their consistency with current veterinary recommendations. Methods An anonymous online questionnaire comprising 41 questions was distributed to Italian dog breeders between October 2023 and March 2024. It collected information on oestrus monitoring, mating and artificial insemination, semen type, pregnancy diagnosis and puppy management until weaning. Of all questionnaires received, 251 met the inclusion criteria. Results The study included 154 breeders from Northern, 49 from Central and 48 from Southern Italy. Management practices were generally homogeneous across areas. Progesterone measurement was used by 96.4% of breeders, although approximately 70% were unaware of the analytical method employed. Natural mating and fresh semen were the preferred reproductive options. Ultrasonography was widely used for pregnancy diagnosis, performed at 26.55 ± 4.84 days after expected ovulation, whereas 87% of breeders requested radiographic foetal counting. Regional differences concerned oestrus detection, diagnostic testing, mating intervals, radiographic timing and puppy weighing frequency. Northern breeders weighed puppies more frequently than Central and Southern breeders (p < 0.001). Conclusion Italian breeders generally follow established reproductive and neonatal practices. Nevertheless, targeted education on progesterone assay interpretation, vaginal cytology and advanced reproductive technologies could improve and standardize breeding management.